Needs Analysis on Developing EFL Essay Writing Materials for 5th Semester of English Department Students - Sunarsih, Wigati; Syarifah, Hanina; Aisyah, Siti Nur (BABASAL English Education Journal, 2024)
The purpose of this research is to provide an understanding of the gap between students' knowledge and skills. This research reveals the target and learning needs of English Education students in semester 5 of Universitas Tidar in the academic year 2023. The respondents who participated were 25 students from Essay Writing class. The method used is descriptive qualitative with two main instruments, namely a questionnaire consisting of seven multiple choice questions and one description question. The results revealed that: (a) in terms of target language needs, the majority of students (32%) want to improve their understanding of paragraph development and understanding of unity and coherence in writing essays; (b) organizing ideas (60%) is a difficulty in writing essays; (c) using the internet (48%) in helping to understand the material in essay writing classes, and choosing to get direction from lecturers (36%). In terms of appropriate teaching methods, the data shows that: (a) dominant students chose internet browsing (56%) as their favorite activity to learn; (b) then (52%) students chose accessing the internet and (32%) chose handouts/modules as effective learning resources for essay writing class. From the data results, it is revealed that internet-based materials are preferred to develop materials in Essay Writing class. In addition, lecturers also have an important role in motivating and directing students in writing essays.